Empirical Evidence Of Oil Price Shocks And Oil Economy Asymmetric Nexus: The Cases Of Angola And Nigeria - Adedeji, Abdulkabir Niran; Ahmed, Funmilola Fausat; Muhammed, Musa (Advances in Social Sciences Research Journal, 2018)
The relationship between oil price shocks and economic growth (GDP) examined in many studies is assumed to be linear. However, this may incorrectly specify if the relationship is nonlinear. The few existing studies that modelled the relationship in dynamic form focused on developed oil-exporting or importing countries leaving dearth of studies on developing oil-backed countries whose oil price fluctuations may be more pronounced. Thus, this study examines asymmetric effects of oil price shocks on economic growth, focusing on Angola and Nigeria. We applied Nonlinear ARDL method to capture both the long- and short-run asymmetric effects with nonlinear error correction in a single equation. GDP and West Texas Intermediate (WTI) and Brent (BRT) oil prices data of 1980-2015 were employed and analyzed. Our results revealed that oil price-growth nexus for Angola and Nigeria is asymmetric. We found that oil prices have significant impacts with positive and negative effects on Nigerian economy, while only negative impact turns to be significant for Angola. Nonetheless, application of expansionary monetary policy for stabilizing these economies to support oil revenue in the wake of oil price fall may have little effect.